A decomposition approach to type 2 interval arithmetic - Piegat, Andrzej; Dobryakova, Larisa (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents multidimensional decomposition RDM type 2 interval arithmetic (D-RDM-T2-I arithmetic), where RDM means relative-distance measure. The decomposition approach considerably simplifies calculations and is transparent for users. Apart from this arithmetic, examples of its applications are also presented. To the authors` best knowledge, no papers on this arithmetic exist. D-RDM-T2-I arithmetic is necessary to create type 2 fuzzy arithmetic based on horizontal [mu]-cuts, which the authors aim to do.
Keywords: multi-dimensional RDM interval arithmetic; type 2 interval arithmetic; RDM type 2 interval arithmetic; decomposition type 2 interval arithmetic; interval arithmetic